Population fecundity of Baltic salmon at artificial and natural reproduction - Mitans, A.R.; Kazanskaya, E.R. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva, 1982)
The size-weight, age and sexual structure of salmon (Salmo salar L.) at artificial and natural reproduction and their individual and population fecundity was studied in the Daugava River (Latvia). It was revealed that the stocked and wild salmon have almost the same indices of individual fecundity and growth in the sea. However the stocked females are characterized by earlier maturation in the sea, their share in the spawning stock is relatively less than that of the wild salmon. It was calculated that the population fecundity of the stocked salmon is by 14 % lower than that of the wild salmon. Further investigations for the optimization of salmon population structure at artificial reproduction are necessary. Published Not Known